Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Review: 18

Answer

$-2 (x+12)(x-3)$

Work Step by Step

$72 - 18x - 2x^2 = -2x^2 - 18x +72 = -2 (x^2 + 9x - 36) = -2 (x^2 + 12x - 3x - 36) = - 2 (x (x+12) - 3 (x + 12)) = -2 (x+12)(x-3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.